1989
DOI: 10.1126/science.2475908
|View full text |Cite
|
Sign up to set email alerts
|

Human KGF is FGF-Related with Properties of a Paracrine Effector of Epithelial Cell Growth

Abstract: Keratinocyte growth factor (KGF) is a human mitogen that is specific for epithelial cells. The complementary DNA sequence of KGF demonstrates that it is a member of the fibroblast growth factor family. The KGF transcript was present in stromal cells derived from epithelial tissues. By comparison with the expression of other epithelial cell mitogens, only KGF, among known human growth factors, has the properties of a stromal mediator of epithelial cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
441
2
4

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 915 publications
(460 citation statements)
references
References 29 publications
13
441
2
4
Order By: Relevance
“…In the co-culture system, there is a very complicated network of autocrine and paracrine secretion like in vivo. The granulosa cells secrete some growth factors, such as fibroblast growth factor 2 (FGF2), fibroblast growth factor 7 (FGF7) and leukemia inhibitory factor (LIF) (Finch et al, 1989;Van Wezel et al, 1995;Nilsson et al, 2002). These growth factors can stimulate the developing embryo.…”
Section: Discussionmentioning
confidence: 99%
“…In the co-culture system, there is a very complicated network of autocrine and paracrine secretion like in vivo. The granulosa cells secrete some growth factors, such as fibroblast growth factor 2 (FGF2), fibroblast growth factor 7 (FGF7) and leukemia inhibitory factor (LIF) (Finch et al, 1989;Van Wezel et al, 1995;Nilsson et al, 2002). These growth factors can stimulate the developing embryo.…”
Section: Discussionmentioning
confidence: 99%
“…11 KGF is synthesized by several mesenchymal cells, such as fibroblasts, 12,15 For KGF to exert its effects, which is mainly in a paracrine manner, KGF needs to bind to its receptor FGFR2-IIIb, which is expressed in keratinocytes and hair follicles. 13,[22][23][24] Activating the KGF receptor leads, through phosphorylation, to proliferation of epithelial cells and is responsible for the morphogenesis of the skin and thus plays an important role during wound healing. 12 After wounding, KGF protein and mRNA concentration increases and they are mainly present in the dermal fibroblasts below the wound and at the wound edges, whereas KGF receptor transcripts and also the corresponding protein were exclusively detected in keratinocytes of the epidermis and the hair follicles.…”
Section: Discussionmentioning
confidence: 99%
“…From previous experiments, we found that KGF, a 26-28 kDa protein, is an epithelial growth factor that exerts its effects mainly in a paracrine manner and is essential for skin morphogenesis. 12,13 KGF has been shown to stimulate epithelial cell differentiation and it appears to control the proliferative-differentiative program from basal to suprabasal cells in the skin. 14 Moreover, KGF stimulates proliferation and exerts an antiapoptotic effect for epithelial cells, which are of major importance for the post-traumatic wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…The keratinocyte growth factor, a member of the fibroblast growth factor family stimulates the proliferation of epithelial cells in vitro and also regulates the proliferation and differentiation of a variety of epithelial tissues in vivo [14,15,16]. In the pancreas, previous works have shown the effect of KGF in ductal-cell proliferation [5].…”
Section: Effect Of Kgf On Beta Cell and Ductal Cell Proliferationmentioning
confidence: 99%